Software agents as legal persons - Andrade, Francisco Carneiro Pacheco (2004)
The Law has long been recognizing that, besides natural persons, other entities socially engaged must also be subject of rights and obligations. Western laws usually recognize Corporate Bodies as having legal personality and capacity for every right and obligation needed or convenient to the prosecution of its social goals. But can we foresee a similar attribution of such a regime to software agents? In other words, are intelligent software agents capable of being personified? One of the main characteristics of a personality is the existence of a physical being or organization provided with its own will. In that sense, intelligent software agents are quite close to human beings. Indeed, they have a physical existence, and they have the capability of learning and of having a will of their own.